Innovative techniques for thread lifting of face and neck. (3rd May 2019) - Rezaee Khiabanloo, Samad; Jebreili, Rogieh; Aalipour, Ezatollah; Eftekhari, Hojat; Saljoughi, Nazi; Shahidi, Arian
Abstract: Background: To investigate the efficacy and outcomes associated with eyebrow, midface, mandibular, and neck lifting using the innovative techniques. Materials and Methods: In this prospective review chart study, a total of 151 patients, were included in the study from January 2016 to May 2017. All participants underwent thread lifting using our innovative thread‐lift technique for head and neck. The patients were followed up first week, first, third, and sixth month after lifting surgery. Outcomes were assessed by two surgeon and patients based on the GAIS score. All data were analyzed by SPSS‐17 software with chi‐square test. Results: A total of 151 patients (mean age: 52.49 ± 10.67, range: 27‐78 years), 16 (10.6%) men and 135 (89.4%) women, were included in the study. The most common sites for the face‐lifting surgery were the mandible (49.7%), midface (37.1%), neck (7.9%), and eyebrow (5.3%), respectively. The level of satisfaction increased from 77.5% in the first week after surgery to 89.4% in the sixth month after surgery for patients, remained unchanged, 96% for the surgeon, and increased from 74.8% to 94.7% for the independent surgeon. The highest rate of potential complications after the lifting surgery was related to ecchymosis (23.2%), followed by complications of tumefaction (6.6%), pain (6.6%), and pain (5.2%). Conclusion: The results showed that the level satisfaction of patients and surgeons increased over time. It seems that facial rejuvenation thread lifting with this innovative technique is effectiveness, safe, and cosmetically more acceptance with minor complications than other face‐lifting techniques.